New Concepts of Optimizing Unit Commitment and Economic Load Dispatch Costs in Large Scale Bower Systems - Ahmed, Musse Mohamud; Ismail, Hassan; Norhamimi, Hamdan (2003)
Using suitable solution techniques to the Unit Commitment (UC) and Economic toad Dispatch (ELD) problems play major role on finding an optimal power scheduling in electrical power system. The UC and ELD problems are to decide. when and which generating units to cornmit and decommit, in order to minimize the total fuel cost over specified period subject to a large number of difficult constraints. Lagrangian Relaxation (LR) has -been widely used to solve UC and ELD. Recently Bundling method (BM) has appeared to be one of the best multipliers updated techniques for LR. This method has promising and the fastest convergence characteristics for UC and ELD problems. For that reason, this paper is to solve the UC and ELD problems via LR, BM and interior point method. This paper explores also the best possible way of updating Lagrangian multipliers with mini" computation time using fast programming techniques